2010
DOI: 10.1128/jb.00022-10
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Plant Pathogen Erwinia amylovora Strain ATCC 49946

Abstract: Erwinia amylovora causes the economically important disease fire blight that affects rosaceous plants, especially pear and apple. Here we report the complete genome sequence and annotation of strain ATCC 49946. The analysis of the sequence and its comparison with sequenced genomes of closely related enterobacteria revealed signs of pathoadaptation to rosaceous hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 5 publications
(2 reference statements)
1
91
0
1
Order By: Relevance
“…An obvious difference between the currently sequenced E. amylovora genomes is the presence of (cryptic) plasmids (Smits et al 2010b;Sebaihia et al 2010;Powney et al 2011). Plasmids appear to be a major factor influencing the pan-genome of E. amylovora.…”
Section: Erwinia Amylovora Genomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…An obvious difference between the currently sequenced E. amylovora genomes is the presence of (cryptic) plasmids (Smits et al 2010b;Sebaihia et al 2010;Powney et al 2011). Plasmids appear to be a major factor influencing the pan-genome of E. amylovora.…”
Section: Erwinia Amylovora Genomicsmentioning
confidence: 99%
“…Nevertheless, the both genomes share over 99.99% sequence identity over the complete length, indicating only minimal evolution since the geographical dispersal. Plasmid pEA72, identified in the genome of E. amylovora Ea273 (Sebaihia et al 2010), is absent in E. amylovora CFBP 1430.…”
Section: Erwinia Amylovora Genomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 3,869 coding sequences (CDS) and putative functions of the encoding genes were automatically assigned to the genome using GenDB (8) with manual optimization (11,12). Plasmid pEA29 shares 99% sequence identity (100% coverage) with previously described pEA29 plasmids in genotypically diverse strains of E. amylovora (6,10,12). Plasmids pEAR5.2 (6 CDS) and pEAR4.3 (4 CDS) are unique to strain ATCC BAA-2158 and share 88% and 89% sequence identity (57% and 53% coverage) with pEP5 of E. pyrifoliae DSM 12163 T (11).…”
mentioning
confidence: 99%
“…The bigger one showed high similarity to plasmids occurring in the human intestinal bacteria. Analysis of genome sequence of the strain Ea273 (well-known and widely used in research) revealed the existence of another new plasmid called AMYP2 (size 71,487 bp) (Sebaihia et al 2010). Recently, a new plasmid of about 60 kbp has also been found in the E. amylovora strain isolated from Sorbus in Poland.…”
Section: Analysis Of Nucleic Acidsmentioning
confidence: 99%